1980
DOI: 10.1073/pnas.77.1.619
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between cytokinin production, presence of plasmids, and fasciation caused by strains of Corynebacterium fascians

Abstract: Cytokinin activity in the culture medium of four pathogenic strains of Corynebacterium fascians varied from 168 to 0.4 jsg of kinetin (6-furfurylaminopurine) equivalents per liter, as compared to 0.2 in an avirulent control. NA-Isopentenyladenine was the predominant cytokinin in the medium of all five strains, and its increased production was correlated with the degree of pathogenicity; however, the virulent strains also produced 8-13 times more cis-zeatin [6(4-hydroxy-3-methyl-cis-2-butenylamino)purineJ than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
1
2

Year Published

1980
1980
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 27 publications
3
39
1
2
Order By: Relevance
“…These strains were unable to fasciate tobacco and geranium (Pelargonium zonale) plants (3). Less-pathogenic strains were also described in later reports on R. fascians (27,31) and do not fasciate tobacco (unpublished data). Therefore, it is tempting to speculate that these isolates lack specifically the downstream genes present in highly virulent strains such as D188.…”
Section: Figmentioning
confidence: 93%
See 1 more Smart Citation
“…These strains were unable to fasciate tobacco and geranium (Pelargonium zonale) plants (3). Less-pathogenic strains were also described in later reports on R. fascians (27,31) and do not fasciate tobacco (unpublished data). Therefore, it is tempting to speculate that these isolates lack specifically the downstream genes present in highly virulent strains such as D188.…”
Section: Figmentioning
confidence: 93%
“…fascians (42) has for a long time been considered as the prototype of a plant-bacterium interaction requiring only cytokinin production to cause neoplastic growth (15). Several cytokinins have been detected in small amounts in the supernatants of some virulent R. fascians cultures (25,30,31) but not in other virulent cultures (1,8), indicating that the phytopathogenicity of R. fascians involves more than mere cytokinin secretion. Indeed, we have previously demonstrated that fasciation is a multigenic trait with determinants located both on extrachromosomal linear plasmids (Fi plasmids) and on the chromosome (8).…”
Section: Figmentioning
confidence: 99%
“…Previous work has shown that several R. fascians strains harbor large plasmids (13,16,17). The presence of a 99-kilobase-pair (kb) plasmid in a strain called MW2 and the simultaneous loss of cadmium resistance, hydrocarbon utilization, and virulence correlated with the loss of this plasmid have been reported by Murai (16).…”
mentioning
confidence: 96%
“…Moreover, it is known that R. fascians can produce at least 11 different cytokinins in vitro (2,18,24,28,48,51). In R. fascians, cytokinins probably originate from two sources, either release from tRNA (36,38) and/or condensation of isopentenyl pyrophosphate and 5Ј-AMP (14). Nevertheless, hitherto no clear correlation between known cytokinins and symptom development could be established (16,18), suggesting that new cytokinin-like molecules could be involved in the formation of the leafy gall (23).…”
mentioning
confidence: 99%